Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.4 - Adding, Subtracting, and Multiplying Radical Expressions - Exercise Set: 49



Work Step by Step

$(\sqrt{5}-\sqrt{2})^{2}$ We can use the formula for squaring a binomial to evaluate this power. The formula is $(a-b)^{2}=a^{2}-2ab+b^{2}$ For this particular case, $a=\sqrt{5}$ and $b=\sqrt{2}$ Substitute the known values into the formula and simplify if possible: $(\sqrt{5}-\sqrt{2})^{2}=(\sqrt{5})^{2}-2(\sqrt{5})(\sqrt{2})+(\sqrt{2})^{2}=...$ $...=5-2\sqrt{10}+2=7-2\sqrt{10}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.